Lecturer’s Competencies and Peer Support on Academic Resilience: The Mediating Role of Self Efficacy - Susanti Kurniawati; Ardika Sulaeman; Arisa Oktaviana Maharani (Economics Education Department Universitas Negeri Semarang, 2026)
This study examines the influence of lecturers' competence and peer support on students' academic resilience, with self-efficacy as a mediating variable. Motivated by rising dropout rates and academic stress in higher education, this research addresses inconsistencies in prior findings on the personal and environmental factors that affect academic resilience. A quantitative explanatory survey was conducted with 285 students in West Java, using a 7-point rating scale questionnaire analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicated that academic resilience and self-efficacy were at moderate levels, while lecturers' competence and peer support were categorized as high. Lecturers' competence, peer support, and self-efficacy affected academic resilience of 0.67, in the strong category. Lecturers' competence did not significantly affect academic resilience directly but exerted a full mediation effect through self-efficacy. In contrast, peer support demonstrated both significant direct and indirect effects on academic resilience through self-efficacy. These findings confirm that strengthening students' internal psychological aspects, particularly self-efficacy, is a prerequisite for external factors such as lecturers' competence to effectively enhance academic resilience.